Efecto de los reguladores de crecimiento ácido naftalenacético y ácido indolbutírico para el enraizamiento de tres especies de crassulaceae - Abarca Zamora, Allison Makevi (2022)
This research was carried out on the "La María" campus, Quevedo State Technical University, located at Km 7.5 Vía Quevedo - El Empalme. The purpose of this research is to evaluate the effect of two growth regulators naphthaleneacetic acid and indolebutyric acid for the rooting of three species of Crassulaceae, we worked with two growth regulators and experimented in various concentrations, Crassulaceae are herbaceous plants with CAM mechanism.